ChemInform Abstract: Neutron Powder Diffraction Study of Ba3ZnRu2‐xIrxO9 (X: 0, 1, 2) with 6H‐Type Perovskite Structure. Issue 8 (February 2016) - Beran, P.; Ivanov, S.a.; Nordblad, P.; Middey, S.; Nag, A.; Sarma, D.d.; Ray, S.; Mathieu, R.
Abstract: Polycrystalline samples of the triple perovskites Ba3 ZnRu2‐x Irx O9 (x = 0, 1, 2) are prepared by calcination of stoichiometric amounts of BaCO3, ZnO, RuO2, and Ir (900 °C, 12 h) and subsequent heating in O2 atmosphere (1150 °C, 72 h).